2007
DOI: 10.1371/journal.pone.0000874
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Genes Activated by the Mitochondrial Unfolded Protein Response (mtUPR) and Cognate Promoter Elements

Abstract: In an accompanying paper, we show that the mitochondrial Unfolded Protein Response or mtUPR is initiated by the activation of transcription of chop through an AP-1 element in the chop promoter. Further, we show that the c/ebpβ gene is similarly activated and CHOP and C/EBPβ subsequently hetero-dimerise to activate transcription of mtUPR responsive genes. Here, we report the discovery of six additional mtUPR responsive genes. We found that these genes encoding mitochondrial proteases YME1L1 and MPPβ, import com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
266
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(271 citation statements)
references
References 28 publications
5
266
0
Order By: Relevance
“…Consistent with this role, several studies have shown that mortalin may be implicated in the progression of neurodegenerative and protein aggregation disorders, such as Parkinson and Alzheimer (Burbulla et al 2010;De Mena et al 2009;Deocaris et al 2008;Deocaris et al 2007;Koren et al 2009;Shi et al 2008). Moreover, when mammalian mitochondria are challenged with an imported protein with a strong tendency to form aggregates, the mitochondrial unfolded protein response (mUPR) is activated (Aldridge et al 2007;Zhao et al 2002). mUPR upregulated the ClpP protease and the cpn60, cpn10, and Tid1 chaperones but not mortalin.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 95%
“…Consistent with this role, several studies have shown that mortalin may be implicated in the progression of neurodegenerative and protein aggregation disorders, such as Parkinson and Alzheimer (Burbulla et al 2010;De Mena et al 2009;Deocaris et al 2008;Deocaris et al 2007;Koren et al 2009;Shi et al 2008). Moreover, when mammalian mitochondria are challenged with an imported protein with a strong tendency to form aggregates, the mitochondrial unfolded protein response (mUPR) is activated (Aldridge et al 2007;Zhao et al 2002). mUPR upregulated the ClpP protease and the cpn60, cpn10, and Tid1 chaperones but not mortalin.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 95%
“…And although CHOP has been associated with neuronal apoptosis after stroke, we observed that in the presence of salubrinal, induction of CHOP-10 protein was not sufficient to cause apoptosis. Aside from its ability to transactivate a group of adaptive genes (Aldridge et al, 2007), CHOP is a known substrate of both p38 and casein II kinase (CKII) (Maytin et al, 2001;Ubeda and Habener, 2003;Wang and Ron, 1996). But, while post-translational modification (PTM) of the CHOP transcriptional activation domain modulates its transcription activation potential, there is no evidence as of yet linking PTMs with target gene selectivity.…”
Section: The Role Of Er-stress Signaling In Hypoxia-induced Apoptoticmentioning
confidence: 99%
“…ATFS1 then enters the nucleus and activates Ubiquitin‐like 5 (UBL5) to form a complex with DVE1 and to induce transcription of mitochondrial chaperones, such as heat shock protein 6 (HSP6) and HSP10 (Haynes, Yang, Blais, Neubert & Ron, 2010; Haynes et al., 2007). In addition, mtUPR induces coenzyme Q biosynthesis, glycolysis, and mitochondrial fission (Aldridge, Horibe & Hoogenraad, 2007), altering mitochondrial metabolism and dynamics to promote mitochondrial function and cell survival during stress. Mitochondrial unfolded protein response and the role of CLPP seem to be conserved in mammals (Benedetti et al., 2006; Zhao et al., 2002), where activation of JNK/c‐JUN pathway leads to the expression of transcription factor C/EBP‐homologous protein (CHOP), which, together with C/EBP, mediates the transcription of mtUPR genes (reviewed in Hill & Van Remmen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is important that, in addition to inducing transcription of over 400 genes, mtUPR in yeast, C. elegans , and mammals are associated with phosphorylation of eukaryotic initiation factor 2 alpha (eIF2a) by general control nonderepressible 2 (GCN2), resulting in global suppression of translation while mRNAs that contain upstream open reading frames (uORFs) are preferentially translated (Delaney et al., 2013; Rath et al., 2012). Transcriptional activation of mtUPR genes and translational suppression seem to be mediated by two parallel mechanisms, both requiring CLPP (Aldridge et al., 2007; Benedetti et al., 2006; Haynes et al., 2007; Zhao et al., 2002) and reviewed in (Jensen & Jasper, 2014; Schulz & Haynes, 2015). It is important that, recessive Clpp mutations have been identified in the human Perrault variant of ovarian failure and sensorineural hearing loss (Jenkinson et al., 2013), and global germline Clpp knockout mice display auditory deficits and complete female and male infertility, in addition to reduced pre/postnatal survival and marked ubiquitous growth retardation (Gispert et al., 2013).…”
Section: Introductionmentioning
confidence: 99%